On the Silk Production of Amasya (1750-1900) - Hüsnü Yücekaya (Gazi Akademik Bakış)
Amasya is one of the most important cities in the chain of Ottoman silk manufacture. From the standpoint of Ottoman silk production, the early role of the city was in the way of being the entrepot of Iranian silk. In later periods, it is reflected in documents that silkworm-breeding and branches of work and production depending on silk reached very important dimensions. It is observed that from the last quarter of the 18th century onward, tax records regarding silk production are mentioned more than the records concerning the tax of mizan-ı harir. It is also observed that at an accelerating rate within the 18th century, records about mulberry fields and wormhouses are intensely mentioned. In line with what has been stated, it is thought that the dependency on Iranian silk decreased in time. Negative effects of the silkworm disease that was effective in the second half of the 19th century were felt in Amasya too. To the degree that it is reflected in the archival material, it is understood that government officials attended perhaps most sensitively to the Amasya silk- production. When examined under the light of the documents and the information, it is thought that there was an Amasya silk production comparable to that of Bursa. Although the city of Bursa played a dominant role in Ottoman silk production, the total production of a few cities such as Amasya was able to nearly balance the Bursa silk production or perhaps provide a production level above that of Bursa.